Glaucoma - the significant challenge for the healthcare system in Poland - Osial, Natalia; Kaczyńska, Agnieszka; Gorecka, Adrianna; Stępień, Piotr; Pożarowska, Dorota; Żarnowski, Tomasz (Journal of Education, Health and Sport, 2022)
Introduction Glaucoma is a group of optic neuropathies characterized by progressive degeneration of retinal ganglion cells (RGCs) and visual field loss. Glaucoma is the leading cause of irreversible blindness in the world. The World Health Organization classifies it as a social and civilization disease and emphasizes the need to improve ophthalmic care systems in order to meet the constantly growing challenge for public health, which is glaucoma. The aim of this article is to identify the main problems that affect the health care system of patients with glaucoma in Poland. Review methods The review of literature on glaucoma was performed using the PubMed and Google Scholar databases. The latest available epidemiological data and the current legal acts concerning the health care system of patients with glaucoma in Poland were also analyzed. Abbreviated description of the state of knowledge The incidence of glaucoma in Poland is constantly increasing, due to the aging of the population. The insidious course of the disease, low public awareness and difficulties in access effective ophthalmic services mean that the disease is diagnosed too late, when significant damage to the optic nerve has already occurred. In addition, the poor mental health of patients, treatment difficulties related to the frequent comorbidity of general diseases and the use of other drug therapies, complicate the course of glaucoma and make it difficult to inhibit its progression. Summary Glaucoma is a significant challenge for public health and the healthcare system in Poland. Therefore, it is very important to take systemic measures as soon as possible that contribute to improve public awareness of eye diseases, increase the availability of ophthalmic care, early detection and appropriate monitoring of the course of glaucoma.